Morning Session Wednesday, June 30,1954 ? BCR?s Role In Building Coal Markets - Harold J. Rose (Rocky Mountain Coal Mining Institute, 1954)
It is a real pleasure to attend another meeting of the Institute. This is partly because I am a Westerner by birth and training. As a young man I had personal experience with firing Colorado and Wyoming coals. The coal industry of the United States has done an outstanding job of producing coal. We can all be proud of the industry's record of continuously adopting technical improvements in coal mining. NEED FOR MORE EFFECTIVE COAL MARKETING However, it cannot be said that the industry has done an equally good job of marketing coal. There has been a rapid growth in U. S. population, and an even greater expansion of industrial demands for heat and power. Yet coal consumption for the past several years has been no greater than it was 40 years ago, in 1912 and 1913.